(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Congenital hypothyroidism (CH) is the most common endocrine disorder in newborns, preventable through early diagnosis, newborn screening, and treatment. CH is characterized by a deficiency of thyroid hormones at birth and is one of the most common causes of preventable mental retardation worldwide. It occurs as a result of underdevelopment of the thyroid gland, insufficient hormone synthesis, or thyroid hormone intolerance. This article discusses congenital hypothyroidism: its main causes, incidence, the effect of thyroid hormone, genetic predisposition, and the possibility of gene linkage.